Polygenic liability for schizophrenia and childhood adversity influences daily‐life emotion dysregulation and psychosis proneness. (21st February 2020) - Pries, L.‐K.; Klingenberg, B.; Menne‐Lothmann, C.; Decoster, J.; van Winkel, R.; Collip, D.; Delespaul, P.; De Hert, M.; Derom, C.; Thiery, E.; Jacobs, N.; Wichers, M.; et al.
Abstract : Objective: To test whether polygenic risk score for schizophrenia (PRS‐S) interacts with childhood adversity and daily‐life stressors to influence momentary mental state domains (negative affect, positive affect, and subtle psychosis expression) and stress‐sensitivity measures. Methods: The data were retrieved from a general population twin cohort including 593 adolescents and young adults. Childhood adversity was assessed using the Childhood Trauma Questionnaire. Daily‐life stressors and momentary mental state domains were measured using ecological momentary assessment. PRS‐S was trained on the latest Psychiatric Genetics Consortium schizophrenia meta‐analysis. The analyses were conducted using multilevel mixed‐effects tobit regression models. Results: Both childhood adversity and daily‐life stressors were associated with increased negative affect, decreased positive affect, and increased subtle psychosis expression, while PRS‐S was only associated with increased positive affect. No gene–environment correlation was detected. There is novel evidence for interaction effects between PRS‐S and childhood adversity to influence momentary mental states [negative affect ( b = 0.07, P = 0.013), positive affect ( b = −0.05, P = 0.043), and subtle psychosis expression ( b = 0.11, P = 0.007)] and stress‐sensitivity measures. Conclusion: Exposure to childhood adversities, particularly in individuals with high PRS‐S, is pleiotropically associated with emotion dysregulation and psychosis proneness.